An inexpensive particle monitor for smoker behaviour modification in homes. Issue 5 (26th September 2012) - Semple, Sean; Apsley, Andrew; MacCalman, Laura
Abstract : Objective: To compare the response of a new particle counting instrument (Dylos DC1700) with that produced by a device (TSI Sidepak Personal Aerosol Monitor AM510) commonly used to measure PM2.5 in settings where secondhand smoke (SHS) is encountered. Methods: Controlled chamber experiments with different SHS concentrations were generated by burning a cigarette for varying time periods and running both devices simultaneously. Results: The Dylos and Sidepak devices produced similar responses to changes in SHS concentrations up to 1000 μg/m 3 . Using 591 min of contemporaneous measurements from 13 chamber experiments, an equation was developed to allow conversion of particle number concentration data from the Dylos to estimated mass concentration data for SHS aerosol. Conclusions: The Dylos DC1700 can provide real-time data that may be converted to an estimate of SHS levels in smoky environments. Given the low cost, low noise and simplicity of use, this device is likely to be a useful tool for interventions to provide feedback of SHS concentrations to help motivate changes in smoking behaviour at home.